Culture-specific items (CSIs) of Eka Kurniawan's Cantik Itu Luka in its English and Russian translations - Korneenkova, Polina; Nugroho, Andy Bayu; Travkin, Pavel (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
This research investigates (1) types of culture-specific items (CSIs), (2) translation techniques applied to CSIs, and (3) translation ideologies employed by the translators of Eka Kurniawan's novel Cantik Itu Luka into its English (Beauty is a Wound) and Russian (Красота – это горе) translations by Annie Tucker and Marina Izvekova, respectively. Using a mixed-methods approach, the study identifies 110 CSIs based on Newmark's classification and analyzes translation techniques through Vinay and Darbelnet’s framework and Venuti’s ideologies of foreignization and domestication. The findings reveal that the culture-specific items (CSIs) identified in the novel fall into several categories: material culture, social culture, organizations, customs, ideas, activities, procedures, concepts, ecology, and gestures and habits. In translating these CSIs, the English version predominantly employed borrowing (39%), amplification (19%), and generalization (13%) techniques. Meanwhile, the Russian translation primarily utilized literal translation (35%), borrowing (28%), and amplification (16%). The English translation's preference for borrowing and amplification techniques aligns with a foreignization ideology, introducing Indonesian culture to English-speaking audiences with minimal alteration. Conversely, the Russian translation leans toward domestication, favoring literal translation (35%) and borrowing (28%) for cultural adaptation.